Fenologia de Caryocar brasiliense Camb. (Caryocaraceae) no Alto Rio Grande, sul de Minas Gerais - Vilela, Gisele Freitas [UNESP]; Carvalho, Dulcineia de; Vieira, Fabio de Almeida (Universidade Federal de Lavras (UFLA), 2008)
Phenological studies are important to understand the dynamics in forest ecosystems and also to enable adequate management of their native species. In the Cerrado regions of the high Rio Grande river (south of Minas Gerais State), Caryocar brasiliense species is found in highly distinct morphological forms with variable phenology. The aim of this study was to investigate phenological patterns within and between populations of both the tree and shrub forms of the individuals and to determine any correlation with abiotic factors. Thirty-five observations of the phenophases of the vegetative and reproductive stages were recorded ever), two weeks for 18 months. The activity index was analyzed for each stage and further analyzed to see if there were associations with the climate data by using Spearman linear correlation. The species was deciduous but leaf growth became retarded during the dry season, at which point leaf flushing stopped and total leaf fall occurred throughout the rainy season. The flowering and the fruit production occurred in the rainy season. The reproductive phase can be either annual or sub-annual. The activity index showed high synchronism within populations during the first flowering in all populations studied (> 80%). Flowering and mature fruits were highly synchronized according to Spearman correlations. Tree and shrub individuals of C. brasiliense had very similar times for their phenophases. The best period for collecting mature fruits in these regions is between February and March.

Estudos fenológicos fornecem subsídios para a compreensão da dinâmica dos ecossistemas florestais e para o manejo de espécies nativas. Na região de Cerrado do Alto Rio Grande, sul de Minas Gerais, a espécie Caryocar brasiliense possui altura e porte variados na maturidade reprodutiva. Objetivou-se, nesse estudo avaliar os padrões fenológicos inter e intrapopulacional dos indivíduos de porte arbóreo e subarbustivo e suas relações com as variáveis climáticas. Foram feitas 35 observações quinzenais das fenofases vegetativas e reprodutivas. Foi analisado o índice de atividade para cada fase, sendo posteriormente correlacionadas com os valores de variáveis meteorológicas com o uso da análise de correlação linear de Spearman. A espécie é caducifólia, com perda total de folhas na estação seca. O enfolhamento cessa durante o período mais seco e inicia-se logo após a queda total das folhas, estendendo-se por toda a estação chuvosa. A floração e frutificação ocorreram durante a estação chuvosa. A fase reprodutiva parece ser anual ou subanual, com mais de um episódio de floração por ano. O índice de atividade revelou alto sincronismo intrapopulacional durante a primeira floração em todas as populações (> 80%). A sincronia interpopulacional para os eventos de floração e frutos maduros foram todas positivas e significativas, conforme as correlações de Spearman. Indivíduos de C. brasiliense de porte arbóreo e porte subarbustivo apresentaram as fenofases em épocas semelhantes. A época ideal para coleta de frutos maduros, nos locais estudados, é nos meses de fevereiro e março.
Phenology of Caryocar brasiliense camb. (caryocaraceae) in the alto rio grande, Minas Gerais state
Keywords: Savanna; Caryocar brasiliense; flowering; fruiting; synchrony